PENDAMPINGAN BELAJAR TEKNIK DASAR SERVIS PENDEK PADA PERMAINAN BULUTANGKIS MELALUI TEMBAK SASARAN BAGI SISWA SD NEGERI 44 PALANGKA - Ahmad Adil; Andi Ihsan; Muh Adnan Hudain; Fahrizal Fahrizal; M Sahib Saleh (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service is motivated by students whose ability to learn basic short serve techniques is still low due to a lack of training in basic techniques for playing badminton. Therefore, the purpose of providing community service assistance in basic short serve techniques for students of SD Negeri 44 Palangka is to improve basic short serve technical skills and students' learning motivation towards Physical Education learning in elementary schools. This can be seen when making observations at SD Negeri 44 Palangka, it can be seen that students cannot do well the basic short serve technique, as the basis for the learning theme of badminton games which aims to improve students' physical fitness and abilities in techniques and tactics of playing badminton as an effort to increase student activity. The learning assistance activities also aim to revive student enthusiasm which decreased during the co-19 pandemic. The method used in tutoring activities is the method of direct practice in the field with the subject matter of the basic techniques of playing badminton with training procedures, namely, heating, core activities and cooling. In the core material, an explanation of the basic techniques is given first, including holding the racket, attitude and body position, foot movements and serving, then students practice the basic techniques that have been explained by the companion of the community service activities. With this tutoring activity, it can increase students' interest in learning about the basic techniques of badminton games. This can be seen from the ability of students responses in the process of tutoring activities in badminton games